Endogenous glucocorticoids control host resistance to viral infection through the tissue-specific regulation of PD-1 expression on NK cells - Quatrini, Linda; Wieduwild, Elisabeth; Escaliere, Bertrand; Filtjens, Jessica; Chasson, Lionel; Laprie, Caroline; Vivier, Eric; Ugolini, Sophie (Nature immunology, 2018)
Controlling the balance between immunity and immunopathology is crucial for host resistance to pathogens. After infection, activation of the hypothalamic–pituitary–adrenal (HPA) axis leads to the production of glucocorticoids. However, the pleiotropic effects of these steroid hormones make it difficult to delineate their precise role(s) in vivo. Here we found that the regulation of natural killer (NK) cell function by the glucocorticoid receptor (GR) was required for host survival after infection with mouse cytomegalovirus (MCMV). Mechanistically, endogenous glucocorticoids produced shortly after infection induced selective and tissue-specific expression of the checkpoint receptor PD-1 on NK cells. This glucocorticoid–PD-1 pathway limited production of the cytokine IFN-γ by spleen NK cells, which prevented immunopathology. Notably, this regulation did not compromise viral clearance. Thus, the fine tuning of NK cell functions by the HPA axis preserved tissue integrity without impairing pathogen elimination, which reveals a novel aspect of neuroimmune regulation. Ugolini and colleagues show that glucocorticoid signaling induces expression of the checkpoint receptor PD-1 on NK cells to control immunopathology in a tissue-specific way.